Commodity price fluctuations and child malnutrition. (October 2022) - Mekasha, Tseday J.; Molla, Kiflu G.; Tarp, Finn; Aikaeli, Jehovaness
Highlights: We examine the potential impacts of international coffee price fluctuations on the nutritional status of children in the 0–5 age category. We show that an upward international coffee price fluctuation is associated with improvement in childhood nutritional status in rural Tanzania. The effect is higher for coffee growers relative to non-growers, though it is not always statistically significant implying spillover effect. Our result underlines the importance of enhancing farmers' coping abilities to manage the adverse impacts of fluctuations in commodity prices. Abstract: In this paper, we empirically examine the potential impact of commodity price fluctuations on the nutritional status of children in the 0–5 age category. This is important as adverse shocks that children experience at the time of birth will have an irreversible long-term impact that can adversely affect subsequent human capital formation. Unlike the bulk of the literature in the area that focuses on the impacts of drought-induced income shocks, we focus on changes in income caused by fluctuations in international coffee prices. We thus aim to estimate the potential impacts of international commodity price fluctuations on the nutritional status of children in commodity-export-dependent developing countries. To this end, we use the three waves of the Tanzanian National Panel Survey (NPS), together with data on international coffee prices. Our results show that an upward coffee price fluctuation is associated with an improvement in childhood nutritional status in rural Tanzania. This result is robust to the inclusion of household (sibling) fixed effects and data choices. The main result of our paper underlines the importance of international commodity price fluctuations for the wellbeing of communities in commodity-export-dependent countries. In the case of Tanzania, for example, the coffee sector creates direct income for about 400, 000 smallholder farmers who produce 90 percent of Tanzania's coffee, which is mainly produced for export. Thus, if not well-managed, international commodity price fluctuations put a strain on the poverty reduction endeavors of developing countries that depend on exports of one or a few non-oil commodities. The results of the paper also have implications for Goal number 2 of the Sustainable Development Goals (SDGs) which aims to end all forms of malnutrition by 2030.